Heterogeneity of Sensory-Induced Astrocytic Ca2+ Dynamics During Functional Hyperemia - Sharma, Kushal; Gordon, Grant R. J.; Tran, Cam Ha T. (Frontiers in Physiology, 2020)
Astrocytic Ca2+ fluctuations associated with functional hyperemia have typically been measured from large cellular compartments such as the soma, the whole arbor and the endfoot. The most prominent Ca2+ event is a large magnitude, delayed signal that follows vasodilation. However, previous work has provided little information about the spatio-temporal properties of such Ca2+ transients or their heterogeneity. Here, using an awake, in vivo two-photon fluorescence-imaging model, we performed detailed profiling of delayed astrocytic Ca2+ signals across astrocytes or within individual astrocyte compartments using small regions of interest next to penetrating arterioles and capillaries along with vasomotor responses to vibrissae stimulation. We demonstrated that while a 5-s air puff that stimulates all whiskers predominantly generated reproducible functional hyperemia in the presence or absence of astrocytic Ca2+ changes, whisker stimulation inconsistently produced astrocytic Ca2+ responses. More importantly, these Ca2+ responses were heterogeneous among subcellular structures of the astrocyte and across different astrocytes that resided within the same field of view. Furthermore, we found that whisker stimulation induced discrete Ca2+ ‘hot spots’ that spread regionally within the endfoot. These data reveal that astrocytic Ca2+ dynamics associated with the microvasculature are more complex than previously thought, and highlight the importance of considering the heterogeneity of astrocytic Ca2+ activity to fully understanding neurovascular coupling.